Prospective study of opportunistic infections among HIV infected patients in VSS Institute of Medical Science and Research, Burla, Sambalpur, Odisha, India - Bariha, P. K.; Mohapatra, M. K.; Kullu, B. K.; Karua, P. C.; Biswal, S. B.; Thakur, A. (International Journal of Advances in Medicine, 2018)
Background: HIV destroys the CD4+T cells progressively thus making the HIV infected persons susceptible to a number of opportunistic infections (OIs). Methods: The study was conducted in the Medicine Department and ART Centre, VIMSAR. It is a prospective study from July 2016 to September 2017. Results: 86 patients register, detail history, clinical examination and investigation were done and then the data is complying in detail. Most of the patients were male (72%) male female ratio is 2.6:1. The majority of patients presented with fever, weight loss and anorexia seen in more than 73% of the study population. Conclusions: (42%) cases belonged to the CD4+T cell count range of 101-200/µl with aCD4+T cell count of 183/µl, so there is increased chance of hospitalization in patients having CD4+T cell count below 200/µl. The most common OI was tuberculosis (51%) with pleural effusion as its commonest manifestation. The second most common OI was candidiasis (43%) with most cases suffering from oral candidiasis was seen to occur at higher CD4+T cell counts than tuberculosis.